Interaction of Intelligence and Learning Psychology for Student Development - Ayu Lillah Amaliyah (Global Journal of Islamic Education, 2025)
The interplay between intelligence and educational psychology plays a crucial role in enhancing student development. This study addresses the issue of inadequate integration of intelligence dimensions cognitive, emotional, and social within psychological frameworks in learning environments. The research aims to analyze how these dimensions interact to support students' academic and personal growth. A qualitative research approach was employed, utilizing semi-structured interviews with educators and educational psychologists, as well as classroom observations across junior high schools. Data collection focused on identifying the practical application of intelligence theories and the influence of psychological principles in shaping effective learning experiences. The findings reveal that cognitive intelligence contributes significantly to problem-solving and critical thinking skills, emotional intelligence fosters resilience and emotional regulation, and social intelligence enhances collaboration and communication. Furthermore, integrating psychological strategies with intelligence dimensions optimizes student engagement and learning outcomes. This study provides empirical evidence supporting the necessity of adaptive teaching methods that incorporate psychological insights to address diverse learning needs. In conclusion, the interaction between intelligence and educational psychology forms a holistic framework that fosters student development, emphasizing the need for educators to balance intellectual, emotional, and social competencies. These findings offer valuable recommendations for enhancing teaching practices and educational policies